2003
DOI: 10.1182/blood-2002-09-2907
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine interactions of basic fibroblast growth factor and interleukin-6 in multiple myeloma

Abstract: Myeloma cells express basic fibroblast growth factor (bFGF), an angiogenic cytokine triggering marrow neovascularization in multiple myeloma (MM). In solid tumors and some lymphohematopoietic malignancies, angiogenic cytokines have also been shown to stimulate tumor growth via paracrine pathways. Since interleukin-6 (IL-6) is a potent growth and survival factor for myeloma cells, we have studied the effects of bFGF on IL-6 secretion by bone marrow stromal cells (BMSCs) and its potential reverse regulation in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
104
0
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 53 publications
5
104
0
8
Order By: Relevance
“…This explains why FGF-2 concentrations in marrow aspirates and peripheral blood correlate with MM activity (Di Raimondo et al, 2000;Sezer et al, 2001;Sato et al, 2002). Bisping et al (2003) have illustrated the expression of highaffinity FGFR-1 through R-4 in RPMI-8226 and U266 MM cell lines and patients' plasma cells, as well as in BMSC, and hence the likelihood of both autocrine and paracrine loops of growth and angiogenesis. Moreover, they demonstrated that FGF-2 induces a time-and dose-dependent increase in IL-6 secretion by BMSC, in the absence of vessels, indicating that its paracrine effects of FGF-2 do not depend on the presence of microvascular EC in the vicinity of plasma cells.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 92%
See 1 more Smart Citation
“…This explains why FGF-2 concentrations in marrow aspirates and peripheral blood correlate with MM activity (Di Raimondo et al, 2000;Sezer et al, 2001;Sato et al, 2002). Bisping et al (2003) have illustrated the expression of highaffinity FGFR-1 through R-4 in RPMI-8226 and U266 MM cell lines and patients' plasma cells, as well as in BMSC, and hence the likelihood of both autocrine and paracrine loops of growth and angiogenesis. Moreover, they demonstrated that FGF-2 induces a time-and dose-dependent increase in IL-6 secretion by BMSC, in the absence of vessels, indicating that its paracrine effects of FGF-2 do not depend on the presence of microvascular EC in the vicinity of plasma cells.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 92%
“…Fibroblast growth factor-2 Plasma cells are the prevailing source of FGF-2 in the bone marrow of patients with active MM Bisping et al, 2003). This explains why FGF-2 concentrations in marrow aspirates and peripheral blood correlate with MM activity (Di Raimondo et al, 2000;Sezer et al, 2001;Sato et al, 2002).…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…bFGF's role in MM-induced angiogenesis has been demonstrated through the capacity of an anti-bFGF blocking antibody to inhibit the in vitro vessel formation induced by BM plasma cell samples [8]. Myeloma cells may produce bFGF, however not all MM patients' plasma cells produce bFGF [41,47,48]. Bisping et al [47] have reported that human myeloma cell lines and sorted CD138 + cells obtained from 12 of 15 MM patients produced bFGF, concluding that myeloma cells are the predominant source of bFGF.…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…Myeloma cells may produce bFGF, however not all MM patients' plasma cells produce bFGF [41,47,48]. Bisping et al [47] have reported that human myeloma cell lines and sorted CD138 + cells obtained from 12 of 15 MM patients produced bFGF, concluding that myeloma cells are the predominant source of bFGF. Others have shown that neither human myeloma cells nor EBV-positive B cell lines secret bFGF [41].…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] The angiogenic switch in MM is mainly sustained by the overproduction of vascular endothelial growth factors (VEGFs) by MM cells and the BM microenvironment. 2,9,10 Other proangiogenic molecules, such as basic fibroblast growth factor, 11,12 interleukin-8 (IL-8), 13 angiopoietin-1 14 and osteopontin 15 are involved in the pro-angiogenic process. Hypoxia is a common feature of solid tumors and is associated with angiogenesis and malignant phenotype.…”
Section: Introductionmentioning
confidence: 99%